EMISSION ANALYSIS ON THE INFLUENCE OF FERROFLUID ON RICE BRAN BIODIESEL - Devarajan, Yuvarajan; Ramanan Madhavan, Venkata (Journal of the Chilean Chemical Society, 2018)
Increase in NOx emission is one of the important drawbacks for using biodiesel as an alternative for petroleum diesel. Several studies had been carried out to reduce the NOx emissions level in biodiesel. The present work is the result of an attempt wherein ferrofluid is added to rice bran oil methyl ester in the way of analyzing its effects on emission characteristics. Magnetite concentrate is exothermic and is known for its characteristics of releasing copious heat at higher temperatures. Nanofluid using magnetite was synthesized by reacting Iron II (FeCl2) and Iron III (FeCl3) in an aqueous ammonia solution to form Magnetite Fe3O4 (Ferro fluid). Release of heat by magnetite during the combustion process would counterbalance the conventional limitations related with biodiesel such as increased delay period, inferior combustion rate and higher NOx emissions etc. Experiments were conducted with Rice Bran Oil Methyl Ester (RBOME) and Rice Bran Oil Methyl Ester with addition of ferrofluid (RBOMEF) and are compared with petroleum diesel. RBOMEF was prepared comprising 97.7% biodiesel, 2% magnetite based ferrofluid and 0.3 % surfactant by volume was used in a Compression Ignition engine. The experimental analysis found a decrease in HC, CO and NOx emissions of 10.8%, 9.1% and 8.49% respectively.